Ecological conflict and ecological harmony in the Berau folktale Bakantan dan Burung Kangkaput: An ecocritical study - Nazwa Aulia; Marwah Ulwatunnisa (Privietlab, 2026)
This article aims to examine the representation of ecological conflict and the meaning of ecological harmony in the Berau folktale Bakantan dan Burung Kangkaput. The study uses a descriptive qualitative method with Greg Garrard’s literary ecocriticism as the analytical framework. The primary data are narrative excerpts, dialogues, and event descriptions from the folktale published in Cerita Rakyat Paser dan Berau. The data were collected through library research, documentation, and repeated close reading, then analyzed using content analysis. The findings show that ecological conflict is represented through three main indicators: ethical failure toward natural abundance, violence against the Kangkaput bird as a nonhuman being, and environmental degradation that affects humans and animals. These findings are interpreted through the concepts of pollution, animals, and earth. Meanwhile, ecological harmony is constructed as a process of restoring damaged relationships among humans, animals, and nature. This harmony appears through human regret, collective animal action, the Kangkaput egg as a symbol of regeneration, moral messages about gratitude and restraint, and the return of prosperity in Berau. Through the relationship between pastoral and dwelling, the folktale shows that harmony is both an image of peaceful coexistence and an ethical way of living responsibly with nature. The study concludes that the folktale criticizes anthropocentric attitudes and affirms the importance of balanced ecological relations.